Enhancing Community Sanitation through the Integration of Istisna and Zakat Financing at Benteng Mikro Tangerang Cooperative - Dina Febriani Darmansyah; Moh Khoirul Anam; M. Reza Prima (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2025)
Zakat funds are essential for supporting social activities. In rural areas, sanitation is a significant concern, making the allocation of zakat funds for sanitation facilities vital. This study aims to evaluate the sanitation program carried out by the Benteng Mikro Tangerang Cooperative and determine the efficiency of this initiative. The data collection involved conducting in-depth interviews with the Cooperative's management. The research findings indicate that both social and commercial funds were combined to develop sanitation in the Benteng Mikro Tangerang Cooperative Community. The Cooperative enhanced the limited social funds by incorporating commercial funds, which significantly boosted the financing for sanitation facilities. This activity also had a commercial impact on the Cooperative, such as facilitating financing distribution and generating profits from fund disbursement. The collection of social funds from the lower economic community was successful, resulting in substantial contributions. Social funds from and for non-Muslims were specifically segregated, and the non-Muslim community showed a high interest in contributing and making donations.